Design, coordination behavior, and spectroscopic discussion of new thymine-azo chelate with an investigation of some of their applications - Mizher, Tabarak Taha; Abbas, Alyaa Khider (Iraqi Journal of Science, 2026)
The thymine-based azo ligand 5-methyl-6-((4-nitronaphthalene-1-yl) diazenyl) pyrimidine-2,4(1H,3H) dione (NAT) was synthesized by diazotization-coupling reaction at room temperature, with its Ag(I) and Cu(II) complexes, subsequently prepared and characterized. Elemental analyses, thermal analyses, and magnetic and molar conductivity confirmed their electrolytic nature, while spectroscopic techniques (FT-IR, HNMR, and UV-Vis and mass spectrometry) revealed structural details. The result appeared that the metal complexes have the molecular formula [Ag(NAT) (H2O)2]NO3.10H2O and [Cu(NAT) (H2O)2] Cl2.10H2O. on the chelating of the ligand (NAT) with metal ions involves the nitrogen donor atom of azo moiety and nitrogen (N1) of pyrimidine moiety which the two complexes have four - coordinated tetrahedral geometry is proposed. The molar conductivity of Ag(I) and Cu(II) complexes appeared with electrolytic properties in nature. When tested as wool fabric dyes, NAT and its complexes displayed vibrant colouration, high durability against abrasion, heat, and washing, and retained a glossy finish.